Предмет: Алгебра,
автор: Tolstolobik3000
доказать тождество:
(a+b)^2 -2b(a+b)=a^2 -b^2
Ответы
Автор ответа:
0
раскладывается по формулам сокращённого умножения.
a^2+2ab+b^2-2ab-2b^2=a^2-b^2 подобные уходят и сокращаются,остаётся
a^2-b^2=a^2-b^2
тождество доказано
a^2+2ab+b^2-2ab-2b^2=a^2-b^2 подобные уходят и сокращаются,остаётся
a^2-b^2=a^2-b^2
тождество доказано
Похожие вопросы
Предмет: Русский язык,
автор: dochanbazilow
Предмет: Русский язык,
автор: begiiiii75
Предмет: Алгебра,
автор: lehaostanech
Предмет: Математика,
автор: ZaRiNa2201015